Septic shock in the intensive care unit of a multidisciplinary hospital - L. L. Plotkin; V. A. Artamonov (Вестник анестезиологии и реаниматологии, 2024)
The objective of the study was to assess the prevalence, etiology, and outcomes of intensive care in patients with septic shock in the ICU of a multidisciplinary hospital.Materials and methods. A single-center, retrospective, cohort study was conducted involving 398 patients with septic shock who were hospitalized in the ICU over a one-year period. Diagnosis of septic shock, as well as a complex of intensive care, were carried out according to the criteria proposed by the recommendations of the Surviving sepsis campaign (2021). Antibacterial therapy was prescribed based on the Guidelines «Diagnosis and antimicrobial therapy of infections caused by multidrug-resistant strains of microorganisms» (2022)Results. The proportion of patients with septic shock was 7.4% of the entire population hospitalized in the ICU. The hospital mortality rate was 25%. The dominant loci of infection in patients with septic shock were the abdominal cavity (33%) and lungs (32.4%). The microbial landscape was dominated by gram-negative flora (66%), among which in 35% of cases, Klebsiella pneumoniae was characterized by resistance to the antibacterial drugs used. Combined antibacterial therapy was received by 84% of patients.